Blockchain Technology in Financial Transactions under Sharia Banking Practice - Wati, Aprilia Candra Purnama; Yazid, Muhammad (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
This research explores the potential impact of blockchain technology on fincancial transactions in Islamic banking, addressing challenges related to security, transparency, and efficiency. Employing a multifaceted approach, the study assesses the benefits of blockchain in Islamic finance through literature reviews and empirical investigations. Notably, blockchain enhances the security of financial transactions by leveraging robust cryptocurrency and decentralized consensus mechanisms, thereby mitigating fraud and manipulation risks. Additionally, blockchain facilitates currency exchange, a critical aspect of Islamic banking, ensuring transparency and adherence to Sharia standards. The research identifies increased efficiency in Sharia banking operations as a key advantage of blockchain technology, attributing it to the automated processes that reduce organizational costs and transaction processing times. Furthermore, blockchain enables more streamlined cross-border transactions, reduces reliance on external entities, and enhances market liquidity. Despite these benefits, the study emphasizes certain challenges in implementing blockchain in Islamic banking, such as the need for youth education, establishing a robust infrastructure, and gaining community trust in new technologies. Successful integration requires collaboration among Sharia banking organizations, regulators, and stakeholders, with clear guidelines and a deep understanding of blockchain innovation. Overcoming these challenges is crucial for unlocking the full potential of blockchain in enhancing the security, transparency, and efficiency of monetary transactions within Islamic finance.